2011
DOI: 10.5606/tjr.2011.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colchicine-Resistant Familial Mediterranean Fever on Growth Parameters

Abstract: Amaç: Bu çalışmada Kolşisin tedavisine dirençli ailesel Akdeniz ateşi (AAA) hastalarında büyüme ve gelişme değerlendirildi. Hastalar ve yöntemler: Ege Üniversitesi Tıp FakültesiÇocuk Nefrolojisi Kliniği'nde Tel Hashomer kriterlerine göre AAA tanısı konulan toplam 87 hasta (45 kız, 42 erkek; ort. yaş 9.6±3.8; dağılım 2-17 yıl) çalışmaya alındı. Atak sırasında hastaların tümünde lökositoz, C-reaktif protein ve fibrinojen seviyesi yüksekliği, artmış eritrosit sedimantasyon hızı ve serum amiloid A seviyesi yüksekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Meanwhile, the growth retardation was attributed to sustained inflammation by the authors. 6 Because colchicine-resistant patients were successfully treated with concomitant canakinumab in our study, we did not investigate colchicine resistance as a parameter on growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the growth retardation was attributed to sustained inflammation by the authors. 6 Because colchicine-resistant patients were successfully treated with concomitant canakinumab in our study, we did not investigate colchicine resistance as a parameter on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies including limited numbers of patients addressed the question whether physical growth is affected by genotype and disease severity or not. [5][6][7][8][9][10] However, all these studies utilized an ancient Tel Hashomer severity scoring system, which was not validated in the pediatric population. 11 Thus, in this study, we aimed to analyze the growth parameters in children with FMF according to disease characteristics including genotype and disease severity by a recently validated tool in relatively more patients.…”
mentioning
confidence: 99%
“…It has been shown that FMF patients catch up to their growth with an effective colchicine treatment [2426]. …”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Pro-inflammatory cytokines may modulate growth patterns in children with inflammatory diseases through both systemic and local effects of the GH/IGF-1 axes [ 23 ]. It has been shown that FMF patients catch up to their growth with an effective colchicine treatment [ 24 26 ].…”
Section: Discussion and Evaluationmentioning
confidence: 99%